A revision of the dark-bellied, stream-dwelling snakes of the genus Hebius (Reptilia: Squamata: Natricidae) with the description of a new species from China, Vietnam and Thailand - David, Patrick; Vogel, Gernot; Nguyen, Truong Quang; Orlov, Nikolai L.; Pauwels, Olivier S. G.; Teynié, Alexandre; Ziegler, Thomas (Zootaxa, 2021)
Species of the genus Hebius Thompson, 1913 with 17 or 19 dorsal scale rows at midbody and an overall dark venter are reviewed, including the two species previously known as Parahelicops annamensis Bourret, 1934 and Pararhabdophis chapaensis Bourret, 1934. Specimens with 17 scale rows are morphologically similar to Hebius venningi (Wall, 1910), which is here redefined based on external morphological characters such as scalation, and dorsal and ventral patterns. Consequently, Natrix nigriventer Wall, 1925 is resurrected from its synonymy with Hebius venningi, whereas Natrix taronensis Smith, 1940, previously considered a subspecies of H. venningi or a full species by some authors but without justification, is here confirmed to full species status. Another group of species, mostly similar in coloration and pattern to the H. venningi group but with 19 dorsal scale rows, includes H. modestus (Günther, 1875), H. deschauenseei (Taylor, 1934) and a new species which is described herein based on specimens from northern Vietnam, southern China and north-eastern Thailand due to distinct morphological differences. We also provide updated taxonomic accounts for the species of this group, including an identification key and distribution maps.